Sistematización y análisis de la evolución de los parámetros ambientales en la central de generación eléctrica de la ciudad de Requena del 2018 - 2021, región Loreto - 2022 - Sangama Correa, Christian Manuel (2022)
The thesis was developed in the Power Plant of the city of Requena, to analyze the evolution of the environmental parameters in its power plant from the environmental monitoring of 2018 -2021. The research is non-experimental, analytical, predictive, horizontal and retrospective. Data variations from 15 quarterly environmental monitoring (04 years) were systematized and analyzed, and based on this analysis of trends and prediction of changes in environmental parameters through mathematical modeling using the Holt-Winters Model with exponential smoothing. The results show that the noise in the Requena power plant has a decreasing trend and the noise levels comply with the environmental quality of the noise, which are not higher than 80 dB. The prediction analysis for the next year reports a descending noise evolution from a maximum level of 61.02 dB to a minimum level of 58.12 dB. In the electromagnetic field, it reports low values according to environmental quality standards for non-ionizing radiation, these values reached are much lower than the maximum level allowed of 4166.67 Volts, which is the maximum level of intensity of non-ionizing radiation. The forecast analysis reports an increasing evolution from a minimum level of 55.55 V/m to a maximum level of 71.07 V/m. Regarding air quality, the evolution of PM-10 particulate material reports values below the National Environmental Quality Standards for Air, which do not exceed 100 ug/m3. The forecast analysis reports a decreasing trend from a maximum level of 43.91 ug/m3 to a minimum level of 36.14 ug/m3.